Uji Aktivitas Antidiabetes Ekstrak Etanol Daun Cengkeh (Syzygium aromaticum) Terhadap Tikus Putih Jantan dan Gambaran Histologi Pankreas - Chemayanti Surbakti; Pricella Aqwilla Br Ginting; Hafizhatul Abadi; Yoksan Duha (Fakultas Farmasi Universitas Setia Budi, 2022)
Diabetes is a chronic disease caused by impaired insulin secretion. WHO has emphasized the use of ethnomedicine for diabetes control. More than 1200 plants have been traditionally used for hypoglycemic effects, of which 800 plants have been scientifically reported to have antidiabetic potential, one of which is clove. Previous research stated that the total flavonoid content in clove leaves was 73.08 mgRE/g extract with a percentage of 7.308%. These flavonoids are thought to be antidiabetic agents. The purpose of this study was to determine the antidiabetic activity of clove leaf ethanol extract and histology of the pancreas of the test rats. Clove leaf simplicia powder was extracted by maceration method using 70% ethanol as solvent. Antidiabetic testing of clove leaf ethanol extract using alloxan at a dose of 150 mg/kgBW. The results showed that clove leaf extract had antidiabetic activity. The percentage decrease in blood sugar levels extract dose 100; 200 and 300 mg/kgBW were 55.61%, 64.06%, and 73.06% and the positive control was 65.83%. The results of histology observations of the pancreas of mice in the negative control group showed that the structure of the islets of Langerhans changed, shrank, irregular, and degenerated cells and pyknosis were found. While the treatment group that was induced by alloxan and given clove leaf extract doses of 100, 200, and 300 mg/kgBW and the positive control showed a clear structure of the islets of Langerhans, more cell mass, cells regenerated and no cells that experienced degeneration and pyknosis were found. The conclusion of this study is that clove leaf extract can reduce blood sugar levels with an effective dose of 300 mg/kgBB and clove leaf extract can improve pancreatic islets of Langerhans cells.